2001
DOI: 10.1128/jvi.75.6.3004-3009.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Accumulation of Hepatitis C Virus Mutations in a Chronically Infected Chimpanzee: Comparison of the Core, E1, HVR1, and NS5b Regions

Abstract: Four hepatitis C virus genome regions (the core, E1, HVR1, and NS5b) were amplified and sequenced from yearly samples obtained from a chronically infected chimpanzee over a 12-year span. Nucleotide substitutions were found to accumulate in the core, E1, and HVR1 regions during the course of chronic infection; substitutions within the NS5b region were not detected for the first 8 years and were found to be minimal during the last 4 years. The rate of accumulation of mutations in the core and E1 regions, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Estimates have ranged from 0.4 ϫ 10 Ϫ3 to 1.9 ϫ 10 (1,20,25,27). The findings in our study suggest that the mutation rate attributable to NS5B miscopying is substantially higher, leading to generation of quasispecies in some regions over a short term.…”
Section: Discussionmentioning
confidence: 56%
“…Estimates have ranged from 0.4 ϫ 10 Ϫ3 to 1.9 ϫ 10 (1,20,25,27). The findings in our study suggest that the mutation rate attributable to NS5B miscopying is substantially higher, leading to generation of quasispecies in some regions over a short term.…”
Section: Discussionmentioning
confidence: 56%
“…The latter represent the consensus sequences of the 12 annual samples. These sequences were identical to those directly determined from PCR products (AF268569∼ AF268580) 40 . In addition, 37 (with “ Ch ” initials) and 53 (with “56” initials) sequences (AY190830∼AY190919) of the same nucleotide range were determined.…”
Section: Resultsmentioning
confidence: 65%
“…A series of archived plasma samples were selected from the same chimpanzee at approximately the same date each year from 1979 to 1990 ( n = 12). Based on these serial samples, the accumulation of HCV mutations in the core, E1 and NS5B regions was evaluated 40 . The remaining cDNAs from the latter study were used as templates in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The genetic heterogeneity of HCV is a result of the high viral replication rate of 10 10 -10 13 viral particles daily 3 together with spontaneous nucleotide substitutions of 10 À2 -10 À3 substitutions per nucleotide per year. 4,5 This suggests that vaccine development should be targeted against genetically stable regions of the HCV genome. It has been shown that DNA immunizations can induce both specific antibodies and cell-mediated responses against the structural and nonstructural (NS) HCV proteins in mice.…”
Section: Introductionmentioning
confidence: 99%